The Utility of Brain CT in Highlighting the Etiological Patterns and Incidental Findings of Traumatic Brain Injury - Arifa Mobeen, Maheen Asif Malik, Mahnoor Sajid, Talha Ali, Tuba Babar, Sania Maqbool, Tamkanat Ilyas, Tamsal Hameed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the utility of brain CT in highlighting the etiological patterns and incidental findings of traumatic brain injury. Methods: From January 2022 to March 2022, 110 patients presenting to emergency department of Pakistan Institute of Neurosciences with brain traumatic injury was present in this study. Patients go through long clinical evaluation and computed tomography on every trauma criteria. Results: The most affected age (group) was 30 to 42 years (37.05%) male (78.2%) to female (21.8%) ratio was 8:2. Injuries were predominantly caused by RTA (72.7%), less commonly caused by fall (11.8%), pedestrial (6.4%), assault (5.5%), and sports (3.6%). Among those with RTA less than 6% people was wearing helmet. The common CT scan evaluation was brain contusion (35%), fracture (13%), Edema (13%), SDH (10%), EDH (8%), SAH (4%), pneumocephalus (5%) and others (3%). Prediction of true prevalence of incidental findings is tough. In this study, we found that enlarged cisterna magna (3.6%) and calcification (3.6%) were the common incidental (findings), and brain tumor (0.9%) and hydrocephalus (0.9%). Conclusion: Road traffic accidents (RTA) are a major cause of TBI. This can be avoided by wearing helmet, but it is less used. Moreover, there is a proper need to put strict system amongst hospitals citywide to lessen the effects of severe TBI. At last every person had to check up on themselves for any minor physical or mental change. Keywords: Traumatic Brain Injury, CT scan, Etiological patterns, Incidental findings.